Building Economic Independence of Islamic Boarding Schools Through the Integration of Digital Business and Entrepreneurship - Heti Hendrayati; Heni Jusuf (Proceeding of International Conference on Islamic Boarding School, 2025)
Islamic boarding schools (pesantren) hold a strategic role in shaping students' character and religious values and fostering socio-economic resilience within communities. Despite their potential, many pesantren still face challenges in achieving financial self-sufficiency. This study investigates the integration of waste management and digital entrepreneurship as a pathway to economic independence for Islamic boarding schools. Utilizing a qualitative case study approach, data were collected from three pesantren through field observations, semi-structured interviews, and document analysis. The findings reveal that daily organic waste, commonly treated as an environmental burden, can be transformed into valuable economic products such as compost, eco-enzymes, and maggot feed. These products, when marketed through e-commerce platforms and supported by sharia-compliantFintech significantly increases institutional revenue. Furthermore, the active involvement of students in business management and digital marketing enhances their entrepreneurial skills and financial literacy. The integration of digital business strategies with sharia-based circular economy practices emerges as a viable model for promoting pesantren economic independence without compromising religious values.